Characterization of the uniform rule with several commodities and agents - Shuhei Morimoto; Shigehiro Serizawa; Stephen Ching (Osaka University, Institute of Social and Economic Research (ISER), 2010)
We consider the problem of allocating infinitely divisible commodities among a group of agents. Especially, we focus on the case where there are several commodities to be allocated, and agents have continuous, strictly convex, and separable preferences. In this paper, we establish that the uniform rule is the only rule satisfying strategy-proofness, unanimity, symmetry, and nonbossiness.
Keywords: C72; D71; 330; strategy-proofness; several infinitely divisible commodities; uniform rule; separable preferences; Güter; Allokation; Nichtkooperatives Spiel; Neue politische Ökonomie; Theorie